Microfinancing : an Islamic law perspective - Fofana, Ibrahim Vamba (Ahmad Ibrahim Kulliyyah of Laws, International Islamic University Malaysia, 2009)
The widespread of Conventional and Islamic based microfinancing and their vital roles in poverty alleviation is undeniable. However, the heart of the matter is that, the Conventional microfinancing has some characteristics that are not in line with the Sharriah principles as it charges interest and focuses mainly on women. Generally, the study starts with a brief introduction of Conventional and Islamic microfinancing together with their concepts, developments, objectives and characteristics. It also discusses the differences between microcredit and microfinancing. Moreover, the study examines the differences between the Islamic microfinancing and Conventional one. For the practices, the study focuses on Grameen Bank of Bangladesh and Amanah Ikhtiar Malaysia (AIM) of Conventional microfinancing. Whereas, for Islamic microfinancing the focus is on Islami Bank Bangladesh Limited (IBBL), SME Bank of Malaysia and EONCAP Islamic Bank Berhad of Malaysia. Furthermore, the study shows that, the applicable contracts of Islamic microfinancing may be divided into two systems. The first one is charitable based-microfinancing system that includes qard hasan contract. The second is profitable based-microfinancing system that includes salam, mudarabah, musharakah, and bay mu'ajjal contracts. At the same time, the study indicates that there are various existing Sharriah compliant contracts that can be useful for Islamic microfinancing institutions (IsMFIs) such as, ijarah, musaqat and muzaraah contracts. Hence, the study also shows that Islamic microfinancing does not charge interest and or focus on mainly the family head as recipient of the loan. It shows that, the zakah and waqf funds can be used for income generation for IsMFIs and for mitigation of the risk. It shows that the kafalah group-based concept can be used as an alternative to collateral, while the service charge can be used as a substitute to interest provided that charge should be of the exact amount of administrative cost. Nonetheless, due to limited resources and time limitation, the study excludes the discussion on the application of Islamic microfinancing in Yemen, Indonesia and other Muslim countries. This study applies qualitative research method and it is theoretical in nature.